Uncanny x-force (2010), volume 1 ebook - Remender, Rick (Uncanny X-Force (2010), 2012)
Collects Uncanny X-Force #1-4. A secret society has resurrected En Sabah Nur, putting into motion events that will turn this age of heroes into an Age of Apocalypse! To hold them back, Wolverine and Archangel bring together Fantomex, Deadpool, and Psylocke to form The Uncanny X-Force! Their mission - kill Apocalypse by any means. Author: Rick Remender. Illustrator: Jermone Opena, Leonardo Manco. © 2020 Marvel Characters, Inc. All rights reserved. All characters featured in this issue and the distinctive names and likenesses thereof, and all related indicia are trademarks of Marvel Characters, Inc. No similarity between any of the names, characters, persons, and/or institutions in this magazine with those of any living or dead person or institution is intended, and any such similarity which may exist is purely coincidental. www.marvel.com.com